Solar powered decentralized water systems: A cleaner solution of the industrial wastewater treatment and clean drinking water supply challenges. (20th March 2021) - Hafeez, Ainy; Shamair, Zufishan; Shezad, Nasir; Javed, Fahed; Fazal, Tahir; Rehman, Saif ur; Bazmi, Aqeel Ahmed; Rehman, Fahad
Abstract: The industrial revolution has created severe water contamination issues due to the release of toxic chemicals into water channels. This crisis has become worst in underdeveloped countries due to the lack of resources and very little implementation of water management policies. The economical water treatment technologies are requisite to resolve water pollution and associated problems. The article deals with two water systems-wastewater and clean drinking water systems, highlights associated problems and discusses the potential instigating factors. Cleaner, sustainable, and energy-efficient solutions for the discussed hitches have been proposed. Aeration technologies being the most energy-intensive operation of the wastewater treatment, have been discussed with their limitations. Mechanical and diffused aerators provide lower standard aeration efficiency while combined aerators are cost-intensive and have limited oxygen mass transfer efficiency, though higher than the former ones. An efficient way of reducing the energy efficiency of the aeration has been proposed by controlling bubble size using a cost-effective technique-Fluidic Oscillator. Therefore, a fluidic oscillator-based aeration system along with the micro-bubbles generation phenomenon and their complexities have been critically deliberated. Purification techniques for drinking water systems have been discussed with a particular focus on sterilization of water through chlorination, chlorine-based compounds, UV radiations, Ultrasonication, and Ozonation. Ozonation using plasma micro-reactor for ozone and reactive species generation for wastewater treatment has been critically discussed. Recent developments in plasma ozonation have been included along with their limitations. Solar integrated cold plasma ozonation has been given special attention as advanced economical water treatment techniques. A decentralized system based on an advanced oxidation reactor capable of producing and dosing oxidation species such as hydroxyl radicals simultaneously in wastewater in-situ has been proposed to provide a clean drinking water supply. A perspective and an integrated strategy have been presented to enhance the efficiency of existing wastewater and water treatment techniques. Graphical abstract: Image 1 Highlights: Oscillatory increases the efficiency of aeration process. Ozone produced by microplasmas enhances energy efficiency of sterilization process. Clean drinking water supply can be ensured using decentralized water systems. Required power for water sterilization should be drawn from solar energy.